Factors affecting excavation using tunnel boring machine [compact disc] : case study - 184264 Ahmad Sayufei Zainuddin (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper ( Sarjana Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005